Identification of Rumen Microbial Genes Involved in Pathways Linked to Appetite, Growth, and Feed Conversion Efficiency in Cattle - Lima, Joana; Auffret, Marc D.; Stewart, Robert D.; Dewhurst, Richard J.; Duthie, Carol-Anne; Snelling, Timothy J.; Walker, Alan W.; Freeman, Tom C.; Watson, Mick; Roehe, Rainer (Frontiers in Genetics, 2019)
The rumen microbiome is essential for the biological processes involved in the conversion of feed into nutrients that can be utilized by the host animal. In the present research the influence of the rumen microbiome on feed conversion efficiency, growth rate and appetite of beef cattle was investigated using metagenomic data. Our aim was to explore the associations between microbial genes and functional pathways, to shed light on the influence of bacterial enzyme expression on host phenotypes. Two groups of cattle were selected on the basis of their high and low feed conversion ratio. Microbial DNA was extracted from rumen samples and the relative abundances of microbial genes were determined via shotgun metagenomic sequencing. Using partial least squares analyses, we identified sets of 20, 14, 17 and 18 microbial genes whose relative abundances explained 63%, 65%, 66% and 73% of the variation of feed conversion efficiency, average daily weight gain, residual feed intake and daily feed intake, respectively. The microbial genes associated with each of these traits were mostly different, but highly correlated traits such as feed conversion ratio and growth rate showed some overlapping genes. Consistently with this result, distinct clusters of a co-abundance network were enriched with microbial genes identified to be related with feed conversion ratio and growth rate or daily feed intake and residual feed intake. Microbial genes encoding for proteins related to cell wall biosynthesis, hemicellulose and cellulose degradation and host-microbiome cross talk (e.g. aguA, ptb, K01188 and murD) were associated with feed conversion ratio and/or average daily gain. Genes related to vitamin B12 biosynthesis, environmental information processing and bacterial mobility (e.g. cobD, tolC and fliN) were associated with residual feed intake and/or daily feed intake. This research highlights the association of the microbiome with feed conversion processes, influencing growth rate and appetite, and it emphasizes the opportunity to use relative abundances of microbial genes in the prediction of these performance traits, with potential implementation in animal breeding programs and dietary interventions.